“Questionnaire of a Speech Genre” of T. V. Shmeleva: Past, Present, Future (for the 30th Anniversary of the Genre Model) - Dementyev, Vadim Viktorovich (Жанры речи, 2020)
The article reflects the scientific fate of the main genre model – the “questionnaire of the speech genre” of T. V. Shmeleva. The author discusses the reasons for the high demand for the “questionnaire” in genre studies: the parameters of the “questionnaire” affect the most important aspects, the “pain points” of the genre; the formal simplicity and consistency of the “questionnaire”. Along with the advantages and achievements (the article gives their brief description), the author points to a few critical issues concerning the “questionnaire”: the lack of items of the “questionnaire” (the juxtaposition of primary and secondary speech genres, direct and indirect speech genres, speech and rhetorical genres, cultural characteristics of speech genres, etc. are not presented in it) and its crucial points which are not commonly recognized, i.e. the ranking points of the “questionnaire”. In relation to modern genre studies, the article deals with the items that either should be or can be, or have already been added to the “questionnaire”, as well as the theoretical justification of their relations, which, according to the author of the article, will allow to clarify some other items of the “questionnaire”. The emphasis is on those points that are less spelled out in the “canonical” “questionnaire”, but that should be used for a more adequate study of genres (especially new ones), and are already actually used. The discussion focuses on the following points: typological, including the stadial-typological and historical-etymological, features of speech genres; determination of the place of the genre in the structural-hierarchical typology; cultural, linguistic and linguocultural characteristics of speech genres; characteristics of the communicative concept, through which the genre is presented and interpreted, and its components; the ability of the genre to form its variants; corpus and quantitative characteristics of speech genre; online genres.